A Review of Mindfulness Therapy to Improve Psychological Well-being During the Covid-19 Pandemic - Widha, Lailatul; Rahmat, Hayatul Khairul; Basri, A Said Hasan (Proceeding International Conference on Science and Engineering, 2021)
Abstract. The existence of Covid-19 is a stressor for individuals which results in psychological problems such as anxiety, fear, and stress. These various psychological problems can affect the body's immunity to fight diseases caused by Covid-19, so it is very important to create a community order that can achieve psychological well-being so that it is tough in facing Covid-19. Efforts to develop psychological well-being in dealing with Covid-19 can be done by utilizing Mindfulness Therapy. The writing of this article uses a literature study. Using mindfulness therapy can effectively develop psychological well-being in dealing with Covid-19.